A342 POST-TREATMENT LIVER STIFFNESS MEASUREMENTS PREDICT THE DEVELOPMENT OF LIVER-RELATED COMPLICATIONS IN PATIENTS WITH HCV CIRRHOSIS WHO ACHIEVE SVR POST-DAA THERAPY. (1st March 2018) - Nguyen, F; Galanakis, C; Cooper, C; Tsien, C
Abstract: Background: Chronic hepatitis C virus (HCV) infection may lead to cirrhosis and liver-related complications (LRC) such as hepatocellular carcinoma (HCC), ascites, hepatic encephalopathy (HE) and esophageal varices. Transient elastography (TE) is a non-invasive measurement of liver fibrosis in HCV, and may predict LRC. HCV therapy with sustained virologic response (SVR) appears to decrease liver stiffness (LS) however, whether this is also associated with fewer LRC is unclear. Aims: To evaluate whether a reduction in LS post-HCV treatment with SVR is associated with a lower incidence of LRC in cirrhotic patients within 24 months of therapy. Methods: We included all cirrhotic patients (LS >12.5 kPa) treated with direct acting antivirals (DAAs) between May 1, 2013 and June 1, 2016 with SVR and pre- and post-treatment TE. We excluded patients with new/worsening LRC before post-treatment TE. Those with baseline LRC were included, and evaluated for worsening LRC, as defined by progression of post-treatment grading of the LRC compared to baseline. The absence of new/worsening LRC was recorded as 'non-event'. ROC curves and Kaplan-Meir analysis were used. Person-time was calculated from the post-treatment TE date to the last clinic visit up to 24 months post-treatment. Results: Of 57 patients, we excluded 4 patients with new LRC prior to post-treatment TE. TE was performed a median 32 weeks after end of treatment (IQR 28.5 weeks). 40/53 (75.5%) patients had reduction in LS, with a mean decrease of 10.7 kPa (SD 10.4). There were no differences in baseline characteristics of patients with/without decreased LS. Post-treatment, 4 events occurred during follow-up: 1 new varices, 1 new HCC, and 2 progression known varices. The incidence rate for patients with increased LS was 0.47/100 person-weeks, vs. 0.19/100 person-weeks for patients with decreased LS (RR 2.5, p=0.40, 95% CI: 0.26–24.0), with no significant difference in mean time to event (74 weeks vs. 79 weeks, respectively, p=0.55). All events occurred in individuals with LS >20.75 kPa, while no events occurred in individuals with LS score <20.75 kPa (4/20 vs. 0/33, p=0.02). This LS cutoff also had the best AUC (0.786) with a sensitivity of 100% and specificity of 67%. Post-treatment, 20/53 (37.7%) patients still had a LS above 20.75 kPa. Conclusions: In our cohort of patients with early cirrhosis (Child-Pugh class A), successful antiviral therapy led to a reduction in LS in most patients. Prior studies have identified a LS cutoff of 20 kPa as associated with clinically significant portal hypertension, and this was confirmed in our post-treatment cohort. Many (37.7%) patients remained above this cut-off and require LRC monitoring post-SVR. The predictive value of long-term, serial LS measurements requires evaluation. Funding Agencies: None